ANÁLISE SOBRE O ENSINO DE EMPREENDEDORISMO E A GERAÇÃO DE INOVAÇÃO NA UNICENTRO - Campos, Gilson Ribas de (2019)
The teaching of entrepreneurship in the university sphere has much influence in the generation of innovations that contribute to the economic and social development in the developed countries. In Brazil, the number of successful cases in entrepreneurship education is still incipient. Brazil needs a better connection between university and society in order to develop the country. In this way, this work aims to analyze the insertion of entrepreneurship in the curricular components of the courses offered by UNICENTRO and the correlation with the results obtained for the technological innovation, either in brands and patents deposited by the institution or generation of incubated companies. The study was limited to a higher education institution in Paraná. This is a descriptive study, with a qualitative approach, with quantitative data collection through research in the University system, analysis of documents such as curriculum of courses, subjects' papers and documents on institution websites, NOVATEC Innovation Agency reports, and data from incubated companies INTEG. In order to do so, the methodological strategy used is to search the respective courses offered by the Institution in the campi of Guarapuava-PR, to identify the disciplines focused on the themes: entrepreneurship, innovation and administration. The main results obtained indicate the data of the courses, the number of hours offered in the subjects of entrepreneurship, the growth of the supply of this type of discipline in the courses through the years. These data, confronted with the number of patents deposited by the University, as well as the number of companies incubated per area, could be analyzed for the discussion and the effective fulfillment of the general objective of this research. As a relevant contribution of the study, it can be arranged to consult the data obtained and subsequent adjustment and restructuring of menus as a way to create yet another innovative environment in the University.